(untitled) (PKP Barcelona 2019 Workshop, 2019)
• Can publish supplementary files, dependent files, and multimedia files • https://journals.lib.sfu.ca/index.php/ifj/article/view/587 • https://journals.lib.sfu.ca/index.php/sfuer/article/view/614/525 • https://journalprivacyconfidentiality.org/index.php/jpc/article/view/722 • Categories can be used to group your articles by theme • https://pubs.lib.umn.edu/index.php/tmq • Plugins can be used to display usage statistics, altmetrics, citations, and other fun things on the article page • https://foodandnutritionresearch.net/index.php/fnr/issue/view/65 • Expanded production workflow in OJS 3.2: • Manage versions of articles • Perform metadata checks before publishing articles • Easily see if and where article is published